2017
DOI: 10.1002/ece3.3533
|View full text |Cite
|
Sign up to set email alerts
|

Senescence and carryover effects of reproductive performance influence migration, condition, and breeding propensity in a small shorebird

Abstract: Breeding propensity, the probability that an animal will attempt to breed each year, is perhaps the least understood demographic process influencing annual fecundity. Breeding propensity is ecologically complex, as associations among a variety of intrinsic and extrinsic factors may interact to affect an animal's breeding decisions. Individuals that opt not to breed can be more difficult to detect than breeders, which can (1) lead to difficulty in estimation of breeding propensity, and (2) bias other demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…A previous study indicated that some non-breeders did not return to the study area (Weithman et al 2017) and thus were not observable, but not all non-breeding plovers were absent from the study area. A previous study indicated that some non-breeders did not return to the study area (Weithman et al 2017) and thus were not observable, but not all non-breeding plovers were absent from the study area.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A previous study indicated that some non-breeders did not return to the study area (Weithman et al 2017) and thus were not observable, but not all non-breeding plovers were absent from the study area. A previous study indicated that some non-breeders did not return to the study area (Weithman et al 2017) and thus were not observable, but not all non-breeding plovers were absent from the study area.…”
Section: Discussionmentioning
confidence: 90%
“…We used estimates of population size from a robust design Barker survival model (Kendall et al 2013, Weithman et al 2017) to calculate population density (adult birds/ha nesting habitat). dry or wet sand, <30% ground cover) was estimated from Pan-sharpened multispectral Quick-Bird (satellite) imagery (1 m resolution) that was classified using Definiens Developer Software (C. Huber, USACE, unpublished data).…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Weithman et al. () additionally interpreted the “availability” parameter ( a ʹ, the probability of being available for capture given that the individual was previously unavailable for capture) as a measure of breeding probability in piping plover ( Charadrius melodus ), a migratory shorebird. The Barker/robust design implemented in program MARK currently lacks multistate and/or multievent extensions, but the multistate extension of the Barker model (Barker, ) allows an alternative, direct means of estimating breeding probability and accommodates uncertain identification of states.…”
Section: Discussionmentioning
confidence: 99%
“…Robust design in combination with auxiliary resightings of live individuals outside of the primary sampling area or period is a very effective way of reducing terminal bias in survival estimates under Markovian temporary emigration (Peñaloza, Kendall, & Langtimm, 2014). Despite the benefits of increased precision of parameter estimates and user-friendly implementation in program MARK (White & Burnham, 1999), the Barker/robust design approach has only rarely been used in empirical applications to estimate survival and population size or density (as derived parameters) of wild animal populations (Fabrizio, Tuckey, Latour, White, & Norris, 2018;Gómez-Ramírez, Gutiérrez-González, & López-González, 2017;Gutiérrez-González, Gómez-Ramírez, López-González, & Doherty, 2015;Ivan, White, & Shenk, 2014;Weithman et al, 2017). Weithman et al (2017) additionally interpreted the "availability" parameter (aʹ, the probability of being available for capture given that the individual was previously unavailable for capture) as a measure of breeding probability in piping plover (Charadrius melodus), a migratory shorebird.…”
Section: Making Use Of Multiple Sampling Occasionsmentioning
confidence: 99%